2019
DOI: 10.1007/s40256-019-00346-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Statins to Reduce All-Cause Mortality in Heart Failure Patients: Findings from the EPICAL2 Cohort Study

Abstract: Introduction The addition of statins to standard care in heart failure (HF) patients remains controversial in clinical practice. Large-scale clinical trials failed to show mortality benefits, but uncertainty persists in real-world settings. Objective We evaluated whether the prescription of statins at hospital discharge is associated with a reduction in all-cause mortality at up to 1 year of follow-up in HF patients. Methods We analyzed data from Epidémiologie et Pronostic de l'Insuffisance Cardiaque Aiguë en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A total of 665 citations were identified, and 210 potentially eligible articles were retrieved in full text. Overall, 54 studies were included in the review ( Figure 1 ) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Risk of bias assessment using NOS showed that the studies have low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 665 citations were identified, and 210 potentially eligible articles were retrieved in full text. Overall, 54 studies were included in the review ( Figure 1 ) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Risk of bias assessment using NOS showed that the studies have low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, there was no significant difference between statin groups in Packer's composite outcome, change in functional class (NYHA), the incidence of hospitalization and cardiovascular events. In cohorts of statin treated HF patients, statin use was not associated with improvement in clinical outcomes nor survival after 1‐year follow‐up in HF with reduced ejection fraction 49,50 . However, in a prior indirect comparative metanalysis, lipophilic statins were reported to reduce cardiovascular and noncardiovascular mortality and hospitalization for worsening HF compared to hydrophilic statins with no difference in cardiovascular hospitalization 15 .…”
Section: Discussionmentioning
confidence: 98%
“…In cohorts of statin treated HF patients, statin use was not associated with improvement in clinical outcomes nor survival after 1-year follow-up in HF with reduced ejection fraction. 49,50 However, in a prior indirect comparative metanalysis, lipophilic statins were reported to reduce cardiovascular and noncardiovascular mortality and hospitalization for worsening HF compared to hydrophilic statins with no difference in cardiovascular hospitalization. 15 Additionally, in a recent comparative study, atorvastatin showed better long-term outcomes, including rehospitalization rates and mortality, compared to rosuvastatin treated HF patients.…”
Section: Discussionmentioning
confidence: 99%